2019
DOI: 10.1111/ics.12567
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds sourced from Terminalia spp. in bacterial malodour prevention: an effective alternative to chemical additives

Abstract: Objective Recently, our group reported that extracts prepared from the Australian native plant Terminalia ferdinandiana Exell. are potent inhibitors of the growth malodorous bacteria with similar efficacy to triclosan and through these results, we highlighted a potential biological alternative to the current chemical additives. Other members of the genus Terminalia are also well documented for their antibacterial potential and tannin contents and thus were investigated as potential deodorant additives. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…essential oils and hydrosol was determined using a modified disc diffusion assay. 22,38 Briefly, 100µL of the each bacterial suspension in log phase was spread onto individual nutrient agar plates and the extracts were tested for antibacterial activity using 5mm sterilised filter paper discs. The discs were each infused with 10µL of the individual plant extract, allowed to dry and placed onto the inoculated plates.…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…essential oils and hydrosol was determined using a modified disc diffusion assay. 22,38 Briefly, 100µL of the each bacterial suspension in log phase was spread onto individual nutrient agar plates and the extracts were tested for antibacterial activity using 5mm sterilised filter paper discs. The discs were each infused with 10µL of the individual plant extract, allowed to dry and placed onto the inoculated plates.…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of each extract was also quantified by disc diffusion assay. 40,41 Graphs of the zone of inhibition (ZOI) versus ln concentration were plotted and MIC values were calculated by linear regression.…”
Section: Disc Diffusion Mic Assaymentioning
confidence: 99%
“…Antimicrobial activity of the kale and spirulina extracts was determined using a modified disc diffusion assay. [43][44][45][46] Briefly, 100µL of the each bacterial suspension in log phase was spread onto individual nutrient agar plates and the extracts were tested for antibacterial activity using 6mm sterilised filter paper discs. The discs were each infused with 10µL of the individual plant extract, allowed to dry and placed onto the inoculated plates.…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of each extract was also quantified by disc diffusion assay. [43][44][45][46] Graphs of the zone of inhibition (ZOI) versus ln concentration were plotted and MIC values were calculated by linear regression.…”
Section: Disc Diffusion Mic Assaymentioning
confidence: 99%
“…The genus Terminalia comprise over 250 species and are well-documented for their use in traditional (Ayurveda) medicines. 1 Investigations into the medicinal potential of these plants has revealed that they not only contain numerous anti-inflammatory and antibacterial compounds [2][3][4][5][6][7] but can prevent the development of cancers, as well as the induction of apoptosis of cancerous cells. 8 Recently, an article that was written by Cock and Cheesman 8 that summarises the available research on Terminalia spp.…”
mentioning
confidence: 99%